Phospholipases: From Structure to Biological Function - Balboa, María A.; Balsinde, Jesús (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Phospholipases are a ubiquitous group of enzymes that hydrolyze ester bonds within membrane phospholipids. These enzymes serve multiple biological functions that go far beyond a mere membrane remodeling role in cellular homeostasis; they also play key functions in nutrient digestion and the regulated formation of bioactive lipids involved in cell signaling. It is to the latter function, critical to life, that this book is primarily concerned with. All the chapters are written by renowned experts in the area, and provide forefront information on the role phospholipases in a number of physiological and pathophysiological settings.